How personality traits are interrelated with team climate and team performance in software engineering?: a preliminary study - Bano Soomro, Arjumand; Salleh, Norsaremah; Nordin, Azlin (2015)
Personality and its impacts on team processes in the domain of software engineering have been an area of investigation for many researchers since the last many years. However, personality traits and its effects on team climate and team performance were not being focused as area of research. In our previous research, we had performed a systematic literature review on team climate and team productivity. In progression of our earlier work in this paper, we have extended the work and take personality traits as an independent variable over team climate and performance. This paper reports the results of preliminary data survey, which has been conducted to measure the effects of personality on team climate and team performance. Results show the strong and positive correlation among personality factor Extraversion, team climate and team performance variables.